ERP Evidence for Ultra-Fast Semantic Processing in the Picture–Word Interference Paradigm - Dell'Acqua, Roberto; Sessa, Paola; Peressotti, Francesca; Mulatti, Claudio; Navarrete, Eduardo; Grainger, Jonathan (Frontiers in Psychology, 2010)
We used the ERP approach combined with a subtraction technique to explore the time-course of activation of semantic and phonological representations in the picture-word interference paradigm. Subjects were exposed to to-be-named pictures superimposed on to-be-ignored semantically related, phonologically related, or unrelated words, and distinct ERP waveforms were generated time-locked to these different classes of stimuli. Difference ERP waveforms were generated in the semantic condition and in the phonological condition by subtracting ERP activity associated with unrelated picture-word stimuli from ERP activity associated with related picture-word stimuli. We measured both latency and amplitude of these difference ERP waveforms in a pre-articulatory time-window. The behavioral results showed standard interference effects in the semantic condition, and facilitatory effects in the phonological condition. The ERP results indicated a bimodal distribution of semantic effects, characterized by the extremely rapid onset (at about 100 ms) of a primary component followed by a later, distinct, component. Phonological effects in ERPs were characterized by components with later onsets and a distinct scalp topography of ERP sources relative to semantic ERP components. Regression analyses revealed a covariation between semantic and phonological behavioral effect sizes and ERP component amplitudes, and no covariation between the behavioral effects and ERP component latency. The early effect of semantic distractors is thought to reflect very fast access to semantic representations from picture stimuli modulating on-going orthographic processing of distractor words.